Optimalization Decisions Of Local Governmental In Indonesia - Suhendro, Saring (E-Jurnal Akuntansi; Vol 32 No 9 (2022)DO - 10.24843/EJA.2022.v32.i09.p15, 2022)
The application of the local government finance system currently being used is one of the facilities from the Ministry of Home Affairs to local governments in the field of regional financial management to strengthen perceptions of regional financial management systems and procedures. This study looks at how task and user characteristics will affect the success of accounting information systems and optimal decision quality of all local governments by adopting the theory of Petter, Delone, and McLean (2013). Data was collected through questionnaires distributed to all residents of the provincial/district/ city governments in Indonesia, as many as 111 units of analysis. The data was processed using Structural Equation Modeling (SEM). This is a cross-sectional study viewed from a time horizon. The results showed a positive effect of task and user characteristics on accounting information systems and optimal head decisions decisions. Keywords: Task Characteristics; User Characteristics; Accounting Information System; Optimal Decision and Local Government.